Impact of Leader-Member Exchange and Perceived Organizational Support on Job Embeddedness: The Moderating Role of Self-Efficacy - Wiedyawati, Rizki Allananda; Zakiy, Muhammad; Tjahjono, Heru Kurnianto (Indatu Journal of Management and Accounting, 2023)
The perception of the relationship between leader-member exchange and good organizational support largely determines an employee’s desire to stay in their jobs. This study aims to examine the effect of leader-member exchange and perceived organizational support on job embeddedness, with self-efficacy as a moderating variable. The study was conducted in three Islamic banks in Indonesia, namely Bank Syariah Indonesia, Bank Madina Syariah, and Bank Muamalat. This research was quantitative, and the sample used comprised 302 respondents obtained through purposive sampling, with data collected using a questionnaire. The results of this study indicate that leader-member exchange and perceived organizational support positively influence job embeddedness in employees. Additionally, this study demonstrates the role of self-efficacy in moderating the relationship between perceived organizational support and job embeddedness. However, self-efficacy could not moderate the relationship between leader-member exchange and job embeddedness. Based on the results of the study, the leaders of Bank Syariah Indonesia, Bank Madina Syariah, and Bank Muamalat must pay attention to fostering good relations between leaders and employees, as well as ensuring positive support from the organization.